Akad Musyarakah In Fatwa Majelis Ulama Indonesia - Azwir Azwir (Proceeding International Seminar of Islamic Studies, 2019)
This paper would like to provide some explanations relating to the development of musyarakah contract in the Indonesian Ulema Council's fatwa after the study found several methods used by MUI in determining fatwa about this musharaka include using the Na? Qathi ', Qauli andapproaches Manhaji. The method or approach used in the determination of this fatwa is by referring to the main legal source and all of these methods or approaches are in accordance with the MUI stipulations in issuing legal edicts.